Kinship Analysis of Several Genotypes of Soybean (Glycine max L. Merrill) Based on Determinants of Kinship Components - Agus Miftakhurrohmat (Nabatia, 2010)
The Success to realize a new superior soybean variety is definitely by a genetic an phenotypic variability. Morphological relationships among soybean genotypes is necessary to orchid breeder in obtaining good hybrids in perennial plants. Openly related among soybean genotypes would increase their crossing opportunity. The aim of this research was to identify morphological relationships of ten soybean genotypes based relative determinant components. The research was carried out on the August until November 2005, at the experiment field of the Jember State Polytechnic and in the Biomolecular Laboratory of the Jember University. The experiment designed in Randomized Block Design (RBD), with ten soybean genotypes as treatment in the three replications. Relationships among of ten soybean genotypes was analyzed according to Cluster Analysis. The result of cluster analysis indicated that, (1) However the genotypes ZKJ 2-3 and ZKJ 1-7 are the most identical on similarity distance 0.0025. On similarity distance more than 0.9965, genotypes ZKJ 1-7 and 482 is different exclusively (2) On minimum distance 0.100 all of genotypes soybean can be divide four groups i.e. Group I (55, 56, 481, 482, Galunggung and 52), group II (ZKJ 2-3 and ZKJ 1-7), group III (I10), and group IV (Lokon).